Pemanfaatan Bookcreator untuk Optimalisasi Literasi Digital Guru dalam Pengembangan Bahan Ajar - Yunianti, Sukma Shinta; Arochman, Taufik (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The rapid development of technology 5.0 requires teachers to have competence in utilizing technology optimally. Teachers are expected to innovate in the learning process, such as developing interactive and interesting teaching materials. Apart from that, there is still a lack of effective learning resources that are ready to use and suit learners’ needs. Moreover, the use of the Merdeka Curriculum requires stakeholders and students to move as dynamically as possible. This certainly hinders the teaching and learning process. Through this activity, teachers are able to create digital teaching materials in the form of e-modules with the help of bookcreator application. The method of this activity is in the form of delivering material, training as well as mentoring, and evaluation. The results of this activity include increasing teachers' skills in creating digital teaching materials. The materials can be used as a learning resource for students. This is in line with the increasing creativity of teachers in utilizing all digital sources as needed as teaching materials